Government Influence on Auditors’ Assessment of Risk of Material Misstatement: A Qualitative Inquiry from Regulatory and Institutional Perspectives - Triyanto, Triyanto; Abdullah, Azizah; Irianto, Gugus; Yulianto, Krist Setyo (Universitas Muhammadiyah Yogyakarta, 2025)
Background: Determining risk of material misstatement (RMM) is a key element in audit quality, but it is still influenced by regulatory factors, auditor competence, and professional culture that are not yet fully optimal in Indonesia.Objective: This study aims to analyse government regulatory factors, individual auditor factors, and cultural factors that influence auditors in determining RMM.Research Method: This study uses an interpretive qualitative approach through in-depth interviews with auditors from PwC, EY, Deloitte, KMPG, DBSD & A and audit regulators (IAPI and OJK).Research Findings: The results show that regulations, auditor competence, and audit culture collectively shape RMM assessments, but are still constrained by inconsistent application of standards, limited competence, and a weak culture of critical thinking.Originality/Novelty of Research: This study offers a holistic perspective by integrating the views of audit practitioners and regulators in understanding the determination of SMR, which is rarely discussed simultaneously in the Indonesian context.